Restrictions and Prohibition of the Use of Hijab on Company Employees: A Human Rights Analysis - Shaiza, Layina; Shivana, Nur (Contemporary Issues on Interfaith Law and Society, 2022)
The prohibition of headscarves in companies has sparked contentious debates surrounding human rights. This study delves into this issue, aiming to scrutinize the prohibition of headscarves in the context of human rights by conducting a comprehensive analysis and comparison of pertinent laws and regulations. It is evident that despite varying perspectives on human rights across different countries, there exists a fundamental entitlement shared by all individuals—the natural rights inherent to humanity. Chief among these natural rights is the right to freedom of religion. In Indonesia, the right to freedom of religion is enshrined in the 1945 Constitution, articulated in Article 28E(1), Article 28E(2), and Article 29(2). Moreover, within the realm of labor relations, Law No. 13 of 2003 concerning Manpower explicitly safeguards against discrimination based on religious attire in the workplace, affirming every worker's entitlement to equal treatment without bias from employers. Furthermore, various regulations promulgated by the United Nations underscore the universality of religious freedom, including the Charter of the Declaration of Human Rights, the 1948 Declaration of Human Rights, the International Covenant on Civil and Political Rights (ICCPR), and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). These international frameworks collectively emphasize the imperative of upholding religious freedom for all individuals worldwide.